2009
DOI: 10.1016/j.bbabio.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase gamma and mitochondrial disease: Understanding the consequence of POLG mutations

Abstract: DNA polymerase γ is the only known DNA polymerase in human mitochondria and is essential for mitochondrial DNA replication and repair. It is well established that defects in mtDNA replication lead to mitochondrial dysfunction and disease. Over 160 coding variations in the gene encoding the catalytic subunit of DNA polymerase γ (POLG) have been identified. Our group and others have characterized a number of the more common and interesting mutations, as well as those disease mutations in the DNA polymerase γ acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
133
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 51 publications
1
133
0
Order By: Relevance
“…mtDNA deletions are associated with several clinical syndromes, but they also increase with age (Krishnan et al 2007). Mutations in nuclear genes involved in mtDNA replication and maintenance, e.g., POLG1 (NM_001126131.1) encoding the catalytic subunit of mitochondrial DNA polymerase g, can cause accumulation of mtDNA point mutations and deletions throughout life (Chan and Copeland 2009). The most common single large-scale mtDNA deletion is 4,977 base pairs (bp) spanning between the genes for cytochrome B (CytB) and cytochrome c oxidase subunit II (COXII) (Krishnan et al 2007;Remes et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…mtDNA deletions are associated with several clinical syndromes, but they also increase with age (Krishnan et al 2007). Mutations in nuclear genes involved in mtDNA replication and maintenance, e.g., POLG1 (NM_001126131.1) encoding the catalytic subunit of mitochondrial DNA polymerase g, can cause accumulation of mtDNA point mutations and deletions throughout life (Chan and Copeland 2009). The most common single large-scale mtDNA deletion is 4,977 base pairs (bp) spanning between the genes for cytochrome B (CytB) and cytochrome c oxidase subunit II (COXII) (Krishnan et al 2007;Remes et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The human POLG gene is located on 15q24-15q26, spans 23 exons and includes a trinucleotide CAG-repeat region that encodes a polyglutamine stretch near the N-terminus of the mature protein, downstream of the presumed mitochondrial targeting sequence. [5][6][7] It has been reported that human cDNA sequences contain 10 consecutive glutamines encoding CAG codons, followed by a single glutamine encoding a CAA codon and then two further CAG codons. 8 Polyglutamine tracts can be sites for protein-protein interactions; altering the tract in POLG may result in suboptimal or improper mtDNA replication.…”
Section: Introductionmentioning
confidence: 99%
“…Alpers syndrome is characterized by refractory seizures, psychomotor regression, and hepatic failure (11,12). Mutation of POLG was first linked to Alpers syndrome in 2004 (13), and to date 45 different point mutations in POLG (18 localized to the polymerase domain) are associated with Alpers syndrome (9,14,15). However, only two Alpers mutations (A467T and W748S, both in the linker region) have been biochemically characterized (16,17).…”
mentioning
confidence: 99%
“…mtDNA depletion syndromes are caused by defects in nuclear genes responsible for replication and maintenance of the mitochondrial genome (7). Mutation of POLG, the gene encoding the catalytic subunit of pol ␥, is frequently involved in disorders linked to mutagenesis of mtDNA (8,9). Presently, more than 150 point mutations in POLG are linked with a wide variety of mitochondrial diseases, including the autosomal dominant (ad) and recessive forms of progressive external ophthalmoplegia (PEO), Alpers syndrome, parkinsonism, ataxia-neuropathy syndromes, and male infertility (tools.niehs.nih.gov/polg) (9).…”
mentioning
confidence: 99%